Production of high nutritional algae as aquaculture feeds. - Wan Omar, Wan Maznah

(untitled)
As the basis of natural food chain~ microalgae play a key role in aquaculture, especially in marine culture as the food soUrce for larvae of many marine species of mollusks, crustaceans and small fish larvae. The importance of algae in aquaculture is not surprising as microalgae are the natural food source of these animals.Although several alternatives exist such as microencapsulated feeds, live microaIgae are still the best and .the most preferred food source.